2013
DOI: 10.1007/s11096-013-9794-8
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of medication reviews in community pharmacies and their effect on potentially inappropriate drug use in elderly patients

Abstract: Additional efforts are needed to improve the implementation of pharmacist-led MRs in order to realize its full potential in general practice, and for a substantial decrease of PIMs to occur in susceptible patients. These efforts should focus on training courses and additional support using computerized systems to share information with GPs and to register MR activities, together with sufficient financial reimbursement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…Training (15). The papers had overlap, but the main issues discussed determined the theme and they have been presented below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Training (15). The papers had overlap, but the main issues discussed determined the theme and they have been presented below.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies found that all drug related hospital admissions are caused by a small number of frequently used drugs. These are anticoagulants, Non-Steroidal Anti Inflammatory Drugs (NSAIDs), opioids and blood glucose lowering drugs [15,16].Yet, multiple medications may improve quality of life and polypharmacy should not be synonymous with poor care [12,17].…”
Section: Polypharmacymentioning
confidence: 99%
“…В обзор включали исследования, в которых производился либо изолированный депрескрайбинг сахароснижающих средств, либо полидепрескрайбинг с выделением подгруппы сахароснижающих средств. Среди 431 ссылки были отобраны 6 исследований [33][34][35][37][38][39], в том числе 1 ран-ОБЗОР ЛИТЕРАТУРЫ КЛИНИЧЕСКАЯ ФАРМАКОЛОГИЯ И ТЕРАПИЯ, 2019, 28 (3) домизированное контролируемое исследование, 1 нерандомизированное сравнительное исследование и 4 неконтролируемых исследования.…”
Section: обзор исследований по депрескрайбингу сахароснижающих средствunclassified
“…В исследовании М. Teichert и соавт. [35] не была подтверждена эффективность анализа лекарственной терапии обученными фармацевтами на основании листа HARM [36] с целью выявления неадекватно назначенных препаратов и их отмены у пациентов в возрасте ≥65 лет, постоянно получавших по крайней мере 5 ЛС.…”
Section: обзор исследований по депрескрайбингу сахароснижающих средствunclassified
“…Medications are essential for the prevention and treatment of disease (2) whereas they can also cause harm due to their adverse effects, medication errors and medication complexity (2) in health services (3). Preventable medication errors are prominent factors in patient safety since improving patient safety and quality of care has become a major focus in healthcare (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%